Characterization and evaluation of glucose oxidase activity in recombinant Saccharomyces cerevisiae strains - Malherbe, Daniel Francois (Stellenbosch : Stellenbosch University, 2010)
Thesis (PhD)--Stellenbosch University, 2010.